Bioactive Compounds and Sensory Quality in Chips of Native Potato Clones (Solanum tuberosum spp. andigena) Grown in the High Andean Region of PERU - Carlos A. Ligarda-Samanez; Henry Palomino-Rincón; David Choque-Quispe; Elibet Moscoso-Moscoso; José C. Arévalo-Quijano; Mary L. Huamán-Carrión; Uriel R. Quispe-Quezada; Jenny C. Muñoz-Saenz; Edgar Gutiérrez-Gómez; Domingo J. Cabel-Moscoso; Reynaldo Sucari-León; Yolanda Aroquipa-Durán; et al. (Foods, 2023)
Native potatoes (Solanum tuberosum spp. andigena) have diverse pigments and are cultivated in Peru’s high Andean regions; they are characterized by containing bioactive compounds that prevent various degenerative diseases. The study aimed to evaluate the physicochemical and sensory quality in chips of native potato clones grown at 3496 m altitude, for which the potatoes were cut into slices and fried in extra virgin olive oil at 180 °C for 200 s. This was determined by proximal analysis, reducing sugars, minerals, color, antioxidant capacity (AC), total phenolic compounds (TPC), and anthocyanins in fresh and chips; an instrumental characterization by FTIR and SEM and sensory tests were also performed. The native potatoes presented low moisture and reduced sugar contents; when frying, their bioactive properties improved, increasing AC, TPC, and trace elements, such as K, Mg, Ca, P, Fe, and Zn. To conclude, fresh clones have high yields in the field and are an essential source of nutrients and bioactive; the salt-free chips of clone B presented better physicochemical properties and greater sensory acceptance, closely followed by clone A. Both clones could be used as raw material by food companies that produce snacks to benefit high Andean agricultural producers.